Phytochemical and Ethnobotanical Study about Tamarisk Gallicain a North Africa South-West of Algeria (Global Journal of Medical Research, 2017)
Abstract not found
Keywords: tamarisk gallica; polyphenols; phytochemical study; chemical valorization; the aerial part